The association between sensory preference and household food waste: evidence from China - Zhang, Li; Ye, Linxiang; Zuo, Xiuping; Qian, Long; Zheng, Manli (Frontiers in Sustainable Food Systems, 2025)
Household food waste contributes to 60% of total global food waste. Based on an online questionnaire survey on household food waste in China, this paper explores the association between sensory preference and household food waste using an Oprobit model. The results show that (1) higher sensory preference scores were associated with higher levels of household food waste. The robustness tests supported this finding. (2) heterogeneity analysis showed that the impact of sensory preference on household food waste varied by the gender, age and education level of respondents, household size, per capita income level, urban–rural type and regional distribution. (3) mechanistic analyses found a moderating effect of food storage technology on the increased food waste effect of sensory preference. Increased food storage technology weakened the effect of sensory preference on household food waste. Therefore, it is necessary to popularize the knowledge of food nutrition and raise the awareness of ‘Love Food, Save Food’ and storage technology to reduce household food waste.